Optimization of the gate assignment problem at Keflavík International Airport - Hanna María Hermannsdóttir 1988- (2015)
The assignment of flights to gates is a complicated and an important scheduling problem that airport management faces daily. The assignment is complex due to different features gates can have and therefore all flights cannot be assigned to all gates. Gate assignments need to be suitable for the airport’s operations and convenient for passengers. For Keflavík international airport (KEF), gates are an extremely limited resource and control the scheduled passenger traffic at the airport. Reaching maximum utilization of this limited resource is therefore very important. Today the assignment at KEF is done manually and nothing is being done to verify if the optimal solution being reached. In this study the current practice of the gate assignment at KEF is examined and outlined. Based on the current practice a binary optimization model is developed. The objectives of the model are to minimize total passenger walking distance, the use of bus and walk-in, walk-out gates and to assign as many sensitive and heavy freight flights to the best suitable gates as possible. The model is tested with two weeks of real data, one week of low season and one of high season period, and the results are compared to the original gate assignment. All solutions are validated using a simulation program, ARCport. The results are promising and show that the developed model can be used to solve the gate assignment problem at KEF, replacing most of the manual work needed to execute the gate assignment. Manual interventions is however needed in some cases when running the model. The use of the model can save the airport time and effort and can possibly result in a better utilization of the airport’s resources. Að úthluta flugum á stæði og hlið er flókið og mikilvægt skipulagsvandamál sem stjórn flugvalla stendur frammi fyrir á hverjum degi. Úthlutunin er flókin vegna mismunandi eiginleika hliða sem gerir það að verkum að ekki er hægt að úthluta öllum flugum á öll hlið. Stæðisúthlutunin þarf að vera viðeigandi fyrir rekstur flugvallarins og ...